Synthesis and Spectral Studies Cu(II) Complexes of 4[N-(2-Hydroxy-1-naphthalidene) Amino] Antipyrine Thiosemicarbazone - Chopra, J.R.; Uppal. U.S. Arora, Divya; Gupta, S.K. (Asian Journal of Chemistry, 2010)
A series of five complexes of Cu(II) with 4[N-(2-hydroxy-1-naphthalidene) amino] antipyrine thiosemicarbazone (HNAAPT) have been reported. Characterisation of these complexes were made on the basis of elemental analysis, molecular weight, magnetic moment, conductivity measurements, infrared and electronic spectra In all the complexes HNAAPT behaves as tridentate (N, N, S) ligand. Thermal properties of these complexes were also investigated.